Understanding of Islamic Studies Through Textual and Contextual Approaches - Hendri Hermawan Adinugraha; Ahmad Hasan Asy’ari Ulama’i (LPPM IAIN Sultan Amai Gorontalo, 2020)
The purpose of this study is to describe Islamic studies through two approaches both are textual and contextual approaches. The method used in this study was a literature research approach. The results of literature research was shown that at current time a religion is always used as the foundation of humanity to answer the complexity of their problems, the Qur’an is always used as the theological and praxis foundation for Muslims in answering it. The form of the Qur’an as a normative text gives rise to multiple interpretations from people who are readers, this results in the emergence of textualist and contextual groups in the scientific domain of Islamic studies. Textualist schools try to purify the practice of the Qur’an through the insider meanings and meanings of the Qur’an itself without involving understanding or reasoning with reality, whereas contextualist schools of thought seek to dialogue the Qur’anic texts with dynamic social realities. Whereas a comprehensive interpretation should be carried out by using two approaches simultaneously in order to produce actual and factual Islamic studies and to make the content of the Qur’an truly relevant to facts or phenomena that are happening anytime and anywhere.